Implementasi Kecakapan Logika dan Kreativitas melalui Humor dalam Materi Teks Anekdot Kelas X SMA dengan Kurikulum Merdeka - Ansori, Redhitya Wempi; Fauzan, Abdul Charis; Fatmawati, Malinda (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The research aim to describe The profiency of logic and creativity in class X anecdotal text material developed in the independent curriculum. The approach and design in this research is qualitative with text analysis as the research objective in the form of content analysis. The results of the study show that the aspects of creativity are accommodated and creativity in learning is related to anecdotal text material in the independent curriculum. Moreover, the exploration of its development is quite explorative by linking anecdotal text material with comedic art that is currently popular, namely stand up comedy.